PENINGKATAN PRODUKSI PADI MELALUI PENERAPAN SRI (SYSTEM OF RICE INTENSIFICATION) DI KABUPATEN SOLOK SELATAN - Joko Adrianto; Harianto Harianto; Manuntun Parulian Hutagaol (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2016)
This study was aimed (1) to analyze factors affecting adoption of System of Rice Intensification (SRI), (2) to measure technical, allocative and economic efficiencies of rice farming (3) to identify the factors that influence the technical inefficiency of rice farming. The data was gather from 90 rice farmers in the study area. The analysis method used are probit fuction model and the stochastic frontier production and frontier cost function. The result showed that variables implementation of SRI was affected by factors such as land, frequency extension, and long periode of farm group membership. The implementation of SRI were able to improve the productivity of rice farming. The level of technical efficiency (TE) was efficient with average TE value either SRI and without SRI rice farming each of 0.88 and 0.89. The level of allocative and economic efficiencies of SRI and without SRI rice farming was inefficient. The average values of allocative efficiency of SRI and without SRI rice farming were each 0.41 and 0.42. The average values of economic efficiency of SRI and without SRI rice farming were each 0.36 and 0.37. Family size was significantly to reduce of level technical inefficiency of SRI and family size, land tenure, farm status was significantly to reduce of level technical inefficiency of without SRI rice farming. Policy implications, the goverment needs to support accessibility and availability of production inputs to enhancement the productivity of rice farming.